Albumin Redox Modifications Promote Cell Calcification Reflecting the Impact of Oxidative Status on Aortic Valve Disease and Atherosclerosis - Tamara Sastre-Oliva; Nerea Corbacho-Alonso; Elena Rodriguez-Sanchez; Elisa Mercado-García; Ines Perales-Sanchez; German Hernandez-Fernandez; Cristina Juarez-Alia; Teresa Tejerina; Luis F. López-Almodóvar; Luis R. Padial; Pedro L. Sánchez; Ernesto Martín-Núñez; et al. (MDPI AG, 2024)
Calcific aortic valve disease (CAVD) and coronary artery disease (CAD) are related cardiovascular diseases in which common mechanisms lead to tissue calcification. Oxidative stress plays a key role in these diseases and there is also evidence that the redox state of serum albumin exerts a significant influence on these conditions. To further explore this issue, we used multimarker scores (OxyScore and AntioxyScore) to assess the global oxidative status in patients with CAVD, with and without CAD, also evaluating their plasma thiol levels. In addition, valvular interstitial cells were treated with reduced, oxidized, and native albumin to study how this protein and its modifications affect cell calcification. The differences we found suggest that oxidative status is distinct in CAVD and CAD, with differences in redox markers and thiol levels. Importantly, the in vitro interstitial cell model revealed that modified albumin affects cell calcification, accelerating this process. Hence, we show here the importance of the redox system in the development of CAVD, emphasizing the relevance of multimarker scores, while also offering evidence of how the redox state of albumin influences vascular calcification. These data highlight the relevance of understanding the overall redox processes involved in these diseases, opening the door to new studies on antioxidants as potential therapies for these patients.